The relationship among intra-group communication, transactive memory systems, collective efficacy and team performance: A structural equation model analysis with Elite Footballers. Issue 4 (3rd April 2023) - Leo, Francisco M.; Filho, Edson; López-Gajardo, Miguel A.; García-Calvo, Tomás; González-Ponce, Inmaculada
ABSTRACT: We explored the relationship among intra-group communication, collective efficacy, transactive memory systems and team performance. One hundred and seventy soccer players, aged between 14 and 38 years ( M  = 18 .35, SD  = 4 .71), from eight national teams participated in this study. Data were analyzed using structural equation modeling. First, our analysis revealed that intra-group communication was positively related to transactive memory systems. Second, transactive memory systems was positively associated with collective efficacy and team performance. Third, our analysis revealed that collective efficacy mediated the relationship between transactive memory systems and performance. Altogether, our findings advance the literature by highlighting the relationship among intra-group communication, collective efficacy, transactive memory systems and team performance team processes. From an applied perspective, our findings suggest that systemic interventions simultaneously targeting various team constructs are important to enhance team functioning. Highlights The relationship among intra-group communication, collective efficacy, transactive memory systems and team performance were examined in national football teams. A cross-sectional design was developed and the data were analyzed using structural equation modeling. Playerś perceptions of high intra-group communication were positively associated with the development of transactive memory systems. Higher levels of transactive memory systems and collective efficacy were associated with better team performance.